Analisis Kinerja Anggaran Pendapatan dan Belanja Daerah Kabupaten Madiun Tahun 2018-2022 - Annisa’ Nur Fitriani; Nur Hayati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the performance of the Madiun Regency regional revenue and expenditure budget (APBD) for the 2018-2022 period using descriptive quantitative methods. Secondary data was taken from the annual report of Madiun Regency's budget realization on the official government website, www.madiunkab.go.id. The results of the analysis show a significant increase in the realization of regional own-source revenue (PAD) and overall regional revenue during the period. There are concerns regarding the low fiscal decentralization ratio and high dependence on transfer revenues from the central government. Despite effective PAD realization, Madiun District has not yet achieved the expected fiscal independence. Expenditure variance analysis revealed large variations between the district's expenditure budget and expenditure realization, highlighting the importance of careful budget planning and efficient financial management. This study concludes that Madiun district needs to increase efforts in developing local revenue sources, reduce dependence on transfer revenues, and improve the efficiency and effectiveness of budget management to achieve better fiscal independence and ensure regional financial sustainability.